Accelerating the impact of financial literacy training programmes on household consumption by empowering women. Issue 29 (21st June 2021) - Koomson, Isaac; Villano, Renato Andrin; Hadley, David
ABSTRACT: This study examines the impact of a joint financial literacy and women's empowerment training programme on household consumption as a welfare indicator. Using data collected from a randomized controlled trial implemented in Ghana, we tested for baseline balance and applied ordinary least squares to estimate endline impact. Our findings revealed that the impact of financial literacy on household consumption is influenced by the design and delivery of the programme. A weaker impact is achieved when financial literacy training is offered alone. The ensuing stronger short-term impact of financial literacy training on household consumption is achieved through the inclusion of a women's empowerment module. The joint delivery of the programme significantly improved household consumption for female-beneficiary and younger households. We advocate the inclusion of women's empowerment training in financial literacy training programmes to accelerate its impact on household welfare through increased household consumption